Listening as Participation: Social Media and Metaphors of Hearing Online - Crawford, Kate (2009)
The popularity of social media forms such as Facebook and Twitter has multiplied the avenues for people to ‘have a voice’ online. But what are the roles of listening in these fora, and how does listening function? This paper examines the concept of listening as a metaphor for forms of receptivity online, and considers the ways in which listening is both present and absent in online participation. The metaphor of listening can offer a productive way to analyse the forms of online engagement that have often been described passively or negatively, such as ‘lurking’, browsing, or non-participation. In particular, this paper develops the concept of listening in social media services: from the ‘background listening’ that may occur between friends, family and acquaintances, to the kinds of ‘active listening’ that are increasingly available to organisations using these technologies. Twitter, the microblogging service, is used as a case study for considering the various forms of listening online, and the different ways it is being adopted by individuals, political parties and companies.